An Examination of Democratic Attitudes of Primary School Teachers - S. Gulec; E.G. Balcik (University of Sofia, 2009)
As democracy can develop better in a society of democratic people, democracy education can also get its intended goals better in a democratic school environment. As the most influential people in a school environment were teachers, this study, too, aimed to determine their levels of democratic attitudes. In the present study, 60 primary school teachers working in the schools attached to the Bursa Metropolitan Municipality were surveyed. The relationships between their attitudes and some variables were studied. These variables included school they work, age, gender, marital status, number of children they have, education level, teaching experience and number of broth-ers or sisters. The questionnaire used for this study was validated by Aydogan & Kukul (2003) based on previous studies made by Gomleksiz (1988), Yildirim (1994) and Atasoy (1997). For the validity of the questionnaire, Cronbach Alpha coefficient (0.829) was calculated. The results suggest that teachers show very positive attitude with a score of 103. When the items were examined individually, some significant relationships were found with the variables. Teachers should have positive democratic attitudes in order to give lessons of democracy to their students. An appropriate and encouraging environment should be prepared in order for students to gain desired democratic outcomes. In a democratic environment, teachers' positive attitudes will help their students to gain critical thinking skills, effective discussion skills, capability for fighting against inequity, cooperation and collaboration skills, and showing empathy and respect for diversity.